Seasonal fluctuation of aerosolization ratio of bioaerosols and quantitative microbial risk assessment in a wastewater treatment plant - Rui-ning Wang; Xiang Li; Cheng Yan (Environmental Science and Pollution Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Response of the microbial community to salt stress and its stratified effect in constructed wetlands - Xinyi Wang; Hui Zhu; Baixing Yan; Brian Shutes; Gary Bañuelos; Rui Cheng (Environmental Science and Pollution Research, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Constructed wetlands integrated with microbial fuel cells for COD and nitrogen removal affected by plant and circuit operation mode - Huiyang Wen; Hui Zhu; Baixing Yan; Brian Shutes; Xiangfei Yu; Rui Cheng; Xin Chen; Xinyi Wang (Environmental Science and Pollution Research, 2021)